Improving The Teachers’ Ability To Develop Independent Curriculum Teaching Modules Through Mentoring Activities In SMA Negeri 1 Asembagus For The Academic Year 2021/2022 - Said Ripin Bukaryo (Al Qalam: Jurnal Ilmiah Keagamaan dan Kemasyarakatan, 2023)
This study aims to improve the ability of SMAN 1 Asembagus teachers to develop teaching modules through mentoring activities. This research is a Suharsimi Arikunto model based school action research (PTS), in which each cycle consists of planning, implementing, observing, and reflecting. This research was conducted in 2 cycles. The subjects of this study were 30 teachers in class X semester I of the 2021/2022 academic year. This study uses a qualitative descriptive analysis technique, which is a research method that describes facts in accordance with the data obtained to identify the level of teachers’ understanding, as well as obtaining the teacher’s response in compiling teaching modules. The data analysis in this study was collected through performance activities, observation sheets, interviews, and documentation. The mentoring activities carried out for class X teachers SMAN 1 Asembagus are possible to improve teachers’ abilities in compiling teaching modules. It is possible to identify from the results of assessments and observations. Before the mentoring was carried out the number of teachers who were able to make teaching modules using an independent curriculum were only 6 teachers (21%) then after cycle II was carried out the number of teachers who were able to make teaching modules increased to 26 teachers (87%). There was an increase in the ability of teachers by 20 people (66%)